Myocardial viability, coronary flow reserve, and in-hospital predictors of late recovery of contractility following successful primary stenting for acute myocardial infarction. Issue 2 (1st February 2003) - Beygui, F; Le Feuvre, C; Helft, G; Maunoury, C; Metzger, J P
Abstract : Objective: To assess the relation between myocardial viability, coronary flow reserve, and recovery of myocardial contractility after stenting for acute myocardial infarction. Design: Consecutive sample prospective study. Setting: University hospital. Patients: 41 patients with single vessel disease and successful primary stenting for a first acute myocardial infarction. Interventions: 201 Tl single photon emission computed tomography, contrast ventriculography, and intracoronary Doppler performed 7 (1) days after primary stenting. Main outcome measures: Regional contractility recovery assessed by contrast ventriculography at 6 (1) months' follow up. Results: On univariate analysis, contractility recovery was correlated to prereperfusion anterograde and collateral flow grades ( r = 0.41, p = 0.03 and r = 0.55, p = 0.0004), viability index ( r = 0.55, p = 0.04), peak creatine kinase concentrations ( r = −0.55, p = 0.0005), left ventricular ejection fraction ( r = 0.45, p = 0.005), end diastolic pressure ( r = −0.62, p < 0.0001), end systolic volume index ( r = −0.47, p = 0.01), and the extent of hypokinetic area ( r = −0.48, p = 0.003), but not the coronary flow reserve. On multivariate analysis, independent predictors of late contractility recovery were prereperfusion anterograde and collateral flow grades and viability index. Relative coronary flow reserve, reflecting the culprit vessel's microvascular function, was correlated only to the extent of the infarct risk area ( r = −0.45, p = 0.003). Conclusions: Independent predictors of contractility recovery between the seventh day and the sixth month after successful stenting for acute myocardial infarction are prereperfusion anterograde and collateral flows and myocardial viability. The culprit vessel's microvascular dysfunction is independent of myocardial viability and contractility and correlated to the extent of "jeopardised microvasculature".